2020
DOI: 10.3386/w27617
|View full text |Cite
|
Sign up to set email alerts
|

Initial Impacts of the Pandemic on Consumer Behavior: Evidence from Linked Income, Spending, and Savings Data

Abstract: Vaidya, and other members of the JP Morgan Chase Institute for their support, contributions, and insights. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w27617.ack NBER working papers are circulated for discussion and comment purposes. They have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 3 publications
0
24
0
1
Order By: Relevance
“…This impact is also evident in household-level bank-account data, as in Bachas et al (2020,) in weekly state-level data, as in Kobayashi et al (2020,) and in the aggregate, as verified by the Bureau of Labor Statistics (2020) analysis in April, which showed that aggregate income rose because of the policy interventions despite the output and consumption decline caused by the restriction measures.…”
Section: Stimulus Checksmentioning
confidence: 64%
“…This impact is also evident in household-level bank-account data, as in Bachas et al (2020,) in weekly state-level data, as in Kobayashi et al (2020,) and in the aggregate, as verified by the Bureau of Labor Statistics (2020) analysis in April, which showed that aggregate income rose because of the policy interventions despite the output and consumption decline caused by the restriction measures.…”
Section: Stimulus Checksmentioning
confidence: 64%
“…Our findings contribute to a recent literature on the measurement of economic indicators in real-time, or at very high frequency. Most of the economic research on the impact of COVID-19 has concentrated on its effect on consumption [6,8,[15][16][17]. We present evidence on the impact of COVID-19 on economic inequality.…”
Section: Discussionmentioning
confidence: 84%
“…Recent research has also used bank account data to study the evolution of different macromagnitudes at very high frequency and, in particular, the effects of the pandemic on consumption [15][16][17]. Our contribution to this literature is threefold.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these cuts were much larger than those that could be explained by the job and income losses occurring at the same time. 2 The drop in consumption regarded households' across the whole income distribution: Bachas et al (2020) and Chetty et al (2020) find that in the US rich individuals cut spending more aggressively and resumed it more slowly compared to low income individuals. This evidence suggests that the consumers' behaviour during the pandemic was affected not only by economic and precautionary motives but also by restrictive policies and infection concerns.…”
Section: Review Of the Literaturementioning
confidence: 99%